The economics of obituaries - Raffaella Intinghero; Pietro Lazzaretto; Paolo Manasse (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2025)
Obituaries are traditionally seen as expressions of grief and remembrance. We argue that they also have an underappreciated economic role: they are vehicles for strategic social and economic signaling. In this paper, we develop a simple theoretical framework in which paid obituaries serve as a form of self-promotion for the authors, especially when the deceased is a prominent public figure. We then test this hypothesis using data from Italy, exploiting the variation in mortality caused by the COVID-19 pandemic as a natural experiment. We show that higher mortality rates are associated with increases in per-capita obituaries, driven not by informational needs but by strategic advertising motives. Our results suggest that obituaries function as a marketplace for visibility and status, where social and economic incentives intersect.
Keywords: A10; A13; D71; D85; D91; 330; Economics of Obituaries; Status Signaling; Social Networks; Media and News; COVID-19; Text Analysis